Socio-economic class affect nutritional status but not food habit - Khattak, Muhammad Muzaffar Ali Khan; Akram, Zenub (Emerald Group Publishing Limited Howard House Wagon Lane Bingley BD16 1WA United Kingdom, 2012)
Purpose of the study The purpose of this study was to compare the nutritional status of two socio-economic classes i.e. upper and middle class females using different approaches apart from body mass index (BMI). Study design Fifty houses were randomly selected from the Scheme, 25 in each class on the basis of rank of the retired military officers. From each house a female in between the age range of 30-50 years was selected and interviewed. Materials and methods The age and anthropometric measurements i.e. weight, height, activity levels and food intakes (for 24 hours recall) were recorded in a questionnaire. For both classes age group (30 13 40 & 41 13 50)and activity levels (light & moderate) were determined. From weight and height data BMI was calculated. The macronutrients namely protein, carbohydrate, fats and micro-nutrients namely minerals, (calcium, phosphorus and iron) and vitamins (A & C) were determined by using the Food Composition Table for Pakistan and compared with norms. Results On overall basis i.e. socio-economic class, age and activity level, the respondents were having increase over reference protein and carbohydrate, while decrease over reference fat intake. The respondents were also having lower calcium and iron intakes by 31-34% and 39-44% respectively. The vitamin A intake was also lower by 22-43%. Conclusions This data suggest that there are faulty food habits and unnecessary restrictions among the females on energy and nutrients intakes in both classes.